Synchronization issues in distributed simulation using Commercial Off-The-Shelf (COTS) simulation packages - Wang, Xiaoguang (2008)
This research focused on the interoperability and synchronization issues in distributed simulation using Commercial-off-the-shelf Simulation Packages (CSPs). A generic architecture was proposed and developed to facilitate and ease the integration of any CSP with an IEEE & OMG standard High Level Architecture (HLA) for distributed simulation. In addition, both conservative and optimistic synchronisation were implemented using HLA capabilities within the generic architecture.